Stop Waiting Problem: Decision Rule with Ψ function and Application with Share Prices - Wolfgang Kohn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper the stop-waiting strategy of Franz Bruss is set into a simple probabilistic framework and applied to the apple share prices from 1984 to 2013. Within the probabilistic framework a heuristic and a mathematical decision rule using the Ψ function is developed. The results are in line with Bruss's theory. We apply the stop-waiting strategy to the Apple share prices and compare the results with a simple start-end and chart technique strategy.
Keywords: C65; E47; G17; 330; Optimal Stopping Problem; Mathematical Tools; Share Market